An Analysis of the Occurrence of Bone Erosion on Computerized Tomography Scans in Allergic Fungal Rhinosinusitis - Muhammad Arif Khan, Muhammad Saleem, Adnan Saleem Umar, Ali Husnain Sheikh, Andleeb Iqbal, Rabia Javed, Khurram Shahzad, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Bone erosion on a CT scan may be an indication of osteoarthritis, rheumatoid arthritis, or bone infections, among other diseases. Tumors and other bone conditions may also be to blame. A doctor would need to analyze the CT scan and maybe do other tests or imaging investigations to identify the source of bone degradation. The study's goal is to examine the prevalence and locations of bone erosion on computed tomography scans in Pakistani patients with allergic fungus rhinosinusitis. Methods: This retrospective observational study was conducted at The study was conducted in PAC Hospital Kamra, Pakistan, between January 2013 and December 2022. 85 of the patients who had bone erosions on a computed tomography scan out of a total of 230 instances of allergic fungal rhinosinusitis were included in the research. Evaluation of bone erosion in various paranasal sinuses and their sub-sites. Patients were categorized into three groups based on how much bone erosion they had: mild, moderate, and severe. Mild instances were those with erosion at a single site, moderate cases had erosion at two subsites, and severe cases had erosion at more than two subsites. Results: In 85 (36.9%) of the patients, bone erosion was discovered after a thorough analysis of the computed tomography scan of the paranasal sinuses. The average impacted age was 23.96 ± 12.71. There were 33 women and 52 men, or 61.1% of the total. The ethmoid sinus was the sinus that had bone erosions the most often. Frontal sinus 24 (16.6%), maxillary sinus 55 (38.19%), sphenoid sinus 27 (18.75%), and maxillary sinus 38 (26.38%) are listed in that order. Out of 85 patients, 15 (17.6%) had a severe illness, 22 (25.8%) had moderate disease, and 48 (56.1%) had mild disease. Implication: The radiological evaluation of illness, regardless of the method and scoring system employed, is crucial because it allows the otolaryngologist and the radiologist to stratify the severity of the disease in instances of AFRS and aids in clinical evaluation and the avoidance of problems Conclusions: Bone erosion occurs frequently in allergic fungal rhinosinusitis. The ethmoid sinus is the most frequently affected paranasal sinus in terms of bone erosion, and computerized tomography (CT) scan is a crucial and efficient inquiry in detecting these erosions. Keywords: rhinosinusitis, bone erosion, sinusitis, radiological evaluation